2013
DOI: 10.1021/ic402710r
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Microstructural Phenomena in Superconducting and Non-superconducting RbxFe2–ySe2: A Transmission Electron Microscopy Study at the Atomic Scale

Abstract: Superconducting (SC) and non-superconducting (non-SC)Rb(x)Fe(2-y)Se2 crystals were grown using the "self-flux" technique in order to assign the microstructural changes to the onset of superconductivity in complex iron selenides. The crystals were thoroughly characterized by magnetic susceptibility and transport measurements as well as powder X-ray diffraction. Special attention was paid to the comparison of the microstructure of the crystals with and without the superconducting transition by means of transmiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…[14,15,16,17] Phase separation in the intercalated iron selenides is well-established and this induction of microscopic domains of minority 122-type structure in a host matrix with robust magnetic properties is unique and interesting. [17,18,19,20,21,22] Though its formation is widely reported, the exact nature of this minority phase remains debated, being described as isostructural with the higher temperature paramagnetic 122 phase from x-ray diffraction on polycrystalline K x Fe 2-y Se 2 or as being distorted to lower orthorhombic or monoclinic symmetries as found in x-ray diffraction on Rb x Fe 2-y Se 2 and Cs x Fe 2-y Se 2 single crystals, respectively. [18,19,23] Other studies of K x Fe 2-y Se 2 have reported the formation of a new '234' phase, which may be unique to the K intercalated family or perhaps simply related to the growth conditions of that particular crystal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14,15,16,17] Phase separation in the intercalated iron selenides is well-established and this induction of microscopic domains of minority 122-type structure in a host matrix with robust magnetic properties is unique and interesting. [17,18,19,20,21,22] Though its formation is widely reported, the exact nature of this minority phase remains debated, being described as isostructural with the higher temperature paramagnetic 122 phase from x-ray diffraction on polycrystalline K x Fe 2-y Se 2 or as being distorted to lower orthorhombic or monoclinic symmetries as found in x-ray diffraction on Rb x Fe 2-y Se 2 and Cs x Fe 2-y Se 2 single crystals, respectively. [18,19,23] Other studies of K x Fe 2-y Se 2 have reported the formation of a new '234' phase, which may be unique to the K intercalated family or perhaps simply related to the growth conditions of that particular crystal.…”
Section: Introductionmentioning
confidence: 99%
“…Superstructure formation due to long range ordering of the Cs vacancies is observed as sharp superlattice reflections in contrast to the commonly seen out-of-plane intensity rods. [18,20,21,26] Modeling based on group theoretical representation analysis shows that three-dimensional Cs vacancy ordering takes place in the ab plane and at alternating layers along the c-axis in both the majority and minority phases.…”
Section: Introductionmentioning
confidence: 99%
“…Along with this, research was conducted on superconductivity of non-cuprate compounds, in particular, of Mg-B, Ba-Na-Ge, Na-WO 3 systems [31,[92][93][94][95][96], as well as iron compounds, ferronickel and iron selenides [97][98][99][100][101][102][103][104][105][106][107][108][109][110]. To date, there is a wide class of such materials which give new opportunities to further increase the transition temperature of the superconductivity with the simultaneous increase in the critical current value.…”
Section: Energy Spectrum Of Superconducting Materials Energy 'Gap' Amentioning
confidence: 99%
“…Subsequently, superconducting Fe compounds were synthesized with Ce, As, F, As, K, Se, Te, Rb, K, Na and other elements [102][103][104][105][106][107][108].…”
Section: Energy Spectrum Of Superconducting Materials Energy 'Gap' Amentioning
confidence: 99%
See 1 more Smart Citation